Implementación de un sistema de control para el bombeo de agua en la comunidad de Patután, cantón Latacunga, provincia de Cotopaxi. - Chicaiza Jami, Joel Danilo (2023)
The purpose of the technological proposal was to implement a system that would allow to start and turn off the water pump located in the community of Patután, Latacunga canton, and thus solve the water shortage that exists in the community. The "Junta de Agua Potable y Saneamiento de Patután" has a water reservoir from where it pumps the water resource, in the machine room it has a centrifugal pump and a board that helped to this end, inside the board it was evidenced that the elements were in bad condition, when using a pump with a power of 25 hp it is required a controlled start that allows to reduce the current peaks. The pumping system must have the necessary elements so that it can operate without compromising the motor, for this purpose equipment was used to protect the integrity of the system. The electronic elements were chosen according to the 25 hp pump and their nameplate data were taken into account. Likewise, calculations were made to corroborate that the elements are sized according to the system, which are: three-phase 56-80 Amp molded case circuit breaker, three-phase 62-73 Amp motor protector, three-phase 42-80 Amp soft starter and other control elements such as push buttons, selectors and relays for starting the pump. Once the elements were obtained we proceeded to the installation of the same, at the moment of starting the pump a gradual start could be observed. Verifying the operation of the system we proceeded to make the measurements with the electronic equipment (amperimetric clamp) the values are similar to the calculated values. Therefore, it could be said that the selected elements are in accordance with the need of the pump.